ASPECTS OF THE IMPLEMENTATION OF SOLAR ENERGY IN THE CONDITIONS OF AVIATION ENTERPRISES - BOYKO, Serhiy; KOTOV, Olesiy; VYSHNEVSKY, Svyatoslav; SHKOKIN, Vadim; HUSAROVA, Oksana (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Taking into account modern realities and the importance of the aviation component in the transport and logistics system of Ukraine, an important factor today is the maintenance of aviation security at the appropriate level of the enterprises of the aviation industry of Ukraine. The research results of various industrial facilities showed that they have different specifics of the technological process and their unique features of the implementation of distributed generation sources. One of the important components in this case is the electricity supply of the specified objects. Meanwhile, there may be some obstacles within the airport territory: natural - terrain relief (highlands, mountains) and high vegetation; artificial - buildings, structures, the height of which is limited by conventional horizontal and inclined planes. The main reason for the growing interest in solar energy is the falling cost of generated electricity. 20 years ago, the production of one kilowatt cost 1 euro. Today, in countries rich in the sun, 1 kW costs less than 10 euro cents, and in some regions 6-7 cents.The possibility and specifics of the operation of a solar power plant (SPP) in the conditions of operating aviation enterprises were analyzed. Therefore, it is possible to consider the airfield area as a potential training ground for the installation of solar photo-electric installations. In order to solve the problem of improving the aviation safety of the objects of the aviation industry of Ukraine, the possibility and peculiarities of the introduction of solar energy in the languages of enterprises of the specified industry were analyzed. A mathematical model of a solar photovoltaic installation was proposed, which makes it possible to evaluate the influence of energy characteristics depending on external factors.
Keywords: decentralized generation; power supply; airfield; airport; solar energy